2013
DOI: 10.1002/stem.1418
|View full text |Cite
|
Sign up to set email alerts
|

Maintenance of stem cell self-renewal in head and neck cancers requires actions of GSK3β influenced by CD44 and RHAMM

Abstract: Cells sorted from head and neck cancers on the basis of their high expression of CD44 have high potency for tumor initiation. These cells are also involved in epithelial to mesenchymal transition (EMT) and we have previously reported that cancer stem cells (CSCs) exist as two biologically distinct phenotypes. Both phenotypes are CD44 high but one is also ESA high and maintains epithelial characteristics, the other is ESA low , has mesenchymal characteristics and is migratory. Examining CD44-regulated signal pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
70
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(72 citation statements)
references
References 47 publications
0
70
0
2
Order By: Relevance
“…Among the most studied receptor proteins are CD44 and receptor for hyaluronan-mediated motility (RHAMM), as they participate in inflammation and cancer motility, migration and metastasis (Slevin et al, 2007; Lokeshwar et al, 2014; Tolg et al, 2014; Misra et al, 2015). Furthermore, both CD44 and RHAMM are associated with the development of stem cell and cancer stem cell (Jiang et al, 2013; Shigeishi et al, 2013; Kouvidi et al, 2014; Jordan et al, 2015). FAK/SRC-mediated ERK activation is involved in signaling event for stem cell development.…”
Section: Ha Receptors and Signalingmentioning
confidence: 99%
“…Among the most studied receptor proteins are CD44 and receptor for hyaluronan-mediated motility (RHAMM), as they participate in inflammation and cancer motility, migration and metastasis (Slevin et al, 2007; Lokeshwar et al, 2014; Tolg et al, 2014; Misra et al, 2015). Furthermore, both CD44 and RHAMM are associated with the development of stem cell and cancer stem cell (Jiang et al, 2013; Shigeishi et al, 2013; Kouvidi et al, 2014; Jordan et al, 2015). FAK/SRC-mediated ERK activation is involved in signaling event for stem cell development.…”
Section: Ha Receptors and Signalingmentioning
confidence: 99%
“…For example, the immunophenotype of cancer stem cells in breast cancer is CD44 ϩ CD24 Ϫ EpCAM ϩ (epithelial cell adhesion molecule) (27) (31,32). In cutaneous SCC cell lines, CD44…”
mentioning
confidence: 99%
“…high EpCAM high population, a shift toward CD44 low cell surface expression, and an increase in the expression of the differentiation marker Calgranulin B (32). EpCAM overexpression contributes to carcinogenesis by inducing anchorage-independent growth and by enhancing proliferation through upregulation of c-Myc and cyclins A and E (33,34).…”
mentioning
confidence: 99%
“…), and is essential in cell migration and proliferation during embryogenesis (12). CD168 has been extensively studied in different tumor cell lines and a variety of tumor types, including lymphoid and myeloid malignancies, and colorectal, breast, ovarian and urothelial carcinoma (13)(14)(15)(16), although only a few studies have dealt with its expression and significance in the head-and-neck SCCs (17)(18)(19). It has been demonstrated that CD168 is required to facilitate proliferation of head-and-neck cancer cells (18).…”
Section: Introductionmentioning
confidence: 99%
“…CD168 is involved in the epithelial-to-mesenchymal transition (EMT) during the process of metastasis, and in the generation of breast cancer stem cells with enhanced resistance to therapy (19).…”
Section: Introductionmentioning
confidence: 99%